DEMAND FORECASTING ANALYSIS WITH DESCRIPTIVE METHODS AND QUALITATIVE APPROACHES TO THE SALE OF BATIK CLOTHING PRODUCTS: ANALISIS FORECASTING DEMAND DENGAN METODE DESKRIPTIF DAN PENDEKATAN KUALITATIF PADA PENJUALAN PRODUK BAJU BATIK - Tabroni Tabroni (Yayasan Education and Social Center, 2022)
The purpose of this analysis is to forecast the sales demand for batik clothes in CIA stores. Storeid uses a descriptive method and a qualitative approach. The data used in this study is primary data in the form of interviews with Business Managers and secondary data in the form of actual sales data for August 2021 - January 2022. There are 3 steps used, namely tabulating sales data in a predetermined period, the second is evaluating tabulation results in graphical form and the last one makes conclusions based on existing data and observations with business owners. The results of this study showed that sales at CIA stores fluctuated where the highest sales were obtained in September where there were 10 long sleeves and 15 short sleeves, while the lowest sales were obtained in December 2021 for long sleeves and in January 2022 for short sleeves. 1 piece. From the results of the analysis, the author concludes that the fluctuating sales results are caused by 3 things, the first is due to the pandemic period which made people implement PSBB, the second is due to technological developments which have caused the spread of market places such as shopee, tokopedia, Bukalapak etc. and the last is due to the use of clothes batik that is only used for certain occasions so that the purchase intensity is low